Peranan Wanita dalam Keseimbangan Kerja-Keluarga berdasarkan Perspektif Islam: Sebuah Kajian Literatur Sistematik: The Role of Women in Work-Family Balance According to the Islamic Perspective: A Systematic Study of Literature - Saleh, Nor Shela; Rosli, Mohd Shafie; Rahman, Riki; Abu Bakar, Thuaibah@Suaibah; Md Ali, Azlah (Journal of Quranic Sciences and Research, 2021)
Economic change is moving the role of women to be holistic and flexible in employment sector engagement. Women are increasingly actively venturing into various fields either as subordinate employees or professional management. The problem arises once there are a handful of working women who fail to balance work and family commitments. In addition, it becomes the trigger of various side effects such as mental health, emotional tension and physiological health problems. Thus, the researcher conducted a systematic review of the literature to look at some of the views of previous researchers related to the issue of family work balance involving women, including in the context of Islamic perspective. Researchers use critical analysis that is to observe the findings of previous researchers. The World Economic Forum shows that Malaysia is ranked 104th in the Global Gender Gap index 2020. The study also found that there are many factors that cause work and family imbalance among working women. Therefore, working women also requisite to ensure that their responsibilities to the family continue to be fulfilled based on the concept of religion. Work and family balance can have a positive impact on women’s well-being and maintain sustainability of work performance as well as commitment to family.